Public Fundraising for Financing Islamic Education and Dakwa Mission - Isbah, M. Falikul (IAIN Surakarta, 2018)
Studies on Islamic education and Islamic propagation (dakwa) have not addressed the aspect of how particular actors fund their missions in Islamic education and dakwa. Based on a case study at Hidayatullah Islamic boarding school or Pesantren Hidayatullah, this article tries to correlate the issue of public fundraising and the financing of Islamic education and dakwa mission in contemporary Indonesia. Pesantren Hidayatullah conducts public fundraising program by forming a charity organization, namely Baitul Maal Hidayatullah (BMH). The finding reveals that the majority of the fund raised from public is used to finance Hidayatullahâ€™s schools and dakwa missions. This finding is in contrast to what have been suggested by other studies stating that charitable fund is supposed to be distributed back to the community based on the need criteria.Â Keywords:Public Fundrising, Islamic Education, Dakwaâ€™